Anemia Status and Water Adequacy with Academic Performance of Obese Children in Bogor - Sanya Anda Lusiana (Aloha International Journal of Health Advancement (AIJHA), 2018)
The objective of this study was to analyze the association between anemia status and water adequacy with academic performance of obese students in elementary schools in Bogor City. The design of this study was cross-sectional and it was conducted in February 2014 until April 2015 in six state and private elementary schools with upper-middle socio-economic level. A total of 204 5th grade obese students and students with normal nutritional status were selected as participants using simple random sampling method. Differences between variables were analyzed by Mann-Whitney test. Correlation between variables was analyzed by chi-square test and logistic regressions test. The results showed that there were significant differences in pocket money and water adequacy between obese and normal students. Anemia anemia status and water adequacy were significantly related to academic performance (p